A study on the sources of job satisfaction of stand-up comedians - Tolentino, Jessica C. (Animo Repository, 2012)
Several studies on job satisfaction were always about the industrial settings in a company. Only a few were done for a stand-up comedians' analysis on what specific factors have greatly affected their performance in their work place. It was the researchers' goal to delve into the stand-up comedians life both personal and work. The researchers were able to gather sufficient data to further support their hypothesis that both context and self-variables contribute to their job satisfaction. Context variables have nine factors of pay, promotion, supervision, fringe benefits, contingent rewards, operating procedures, co-workers, nature of work and communication from Paul Spector's Job Satisfaction Survey where the researchers used this to screen over a hundred respondents. On the other hand, self-variables are humor, motivation and positive disposition.